(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This paper analyzes the issues of plot and conflict in O’tkir Hoshimov’s novel "Lives Passed in a Dream." In the work, the plot is constructed based on real-life events and develops through the contradictions between human fate, society, and the individual. The novel’s plot is enriched not so much by sequential events as by the characters’ inner experiences, psychological struggles, and life choices. Conflicts are primarily internal (psychological) and external (social) in nature, serving to reveal the main characters’ spiritual quests, pangs of conscience, and the problems of the era.